Empirical Review of the Challenges of the Cashless Policy Implementation in Nigeria: A Cross-Sectional Research. (August 2019) - Ejiobih, Chukwuebuka; A.Oni, Aderonke; Ayo, Charles K.; Bishung, Janet; Ajibade, Adejoke; Koyejo, Ooreofe; Olushola, Austin
Abstract: Since the implementation of the cashless policy on January 1 st, 2012 in Lagos state which is aimed at reducing the high cost of cash production, circulation and distribution in Nigerian economy, the set-out goals have not been fully achieved due to several on-going challenges. This survey research was conducted to review challenges of the cashless policy implementation in Nigeria and to identify factors that influence the adoption of electronic payment for exchange of value. The Unified Theory of Acceptance and Usage of Technology (UTAUT) was employed to identify various challenges from data gathered through questionnaires distributed to different stakeholders in the economy. A total of 410 questionnaires were collected and the research work adopted used Partial Least Square (PLS) method and used SmartPLS software during the data analysis. The attendant findings were pivotal to understanding the challenges encountered in implementing cashless policy in Nigeria. Using UTAUT we measured the significance and impact of Social Influence, Facilitating Condition, Effort Expectancy, Performance Expectancy and Behavioural Intent to Use on Actual User Adoption. From the result, facilitating conditions has no direct effect on actual system use and trust has no positive effect on behavioural intention to adopt the system. This study shows that despite the implementation of this policy, a lot of users are still being faced with various challenges and more efforts are still being required to achieve an effective cashless society.